Pharmacy Practice and Education in Latvia - Ruta Muceniece; Una Riekstina; Baiba Maurina; Vija Enina; Jeffrey Atkinson (MDPI AG, 2018)
The PHARMINE ("Pharmacy Education in Europe") project studied the organisation of pharmacy practice and education in the member states of the European Union (EU). The work was carried out using an electronic survey sent to chosen pharmacy representatives. The surveys of the individual member states are now being published as reference documents. This paper presents the results of the PHARMINE survey on pharmacy practice and education in Latvia. In the light of this, we examine the harmonisation of practice and education in Latvia with EU norms.